Percutaneous Transhepatic Cholangiography, Percutaneous Biliary Drainage and Metallic Endoprotesis Applications in Malign Biliary Obstructions - Gülşah Bayram Ilıkan; İlkay Akmangit (Journal of Contemporary Medicine, 2021)
Objective:We aimed to present the effectiveness of percutaneous transhepatic cholangiography, percutaneous biliary drainage and metallic endoprotesis applications in patients with inoperable biliary obstructions. Materials and Methods: Percutaneous transhepatic cholangiographies(PTC) and percutaneous biliary drainages (PBD) were performed in 44 patients with inoperabl malignant obstructive jaundice who had been hospitalized in the radiology department of our hospital over a three years period. Six patients (13.6%) underwent external biliary drainage(EBD), 27 patients (61.4%) underwent internal-external biliary drainage(I-EBD) and metallic stents were placed in 11 patients (25%) on average 6 days (1-34 days) after I-EBD. The mean total bilirubin(TB), ALP, ALT, AST, GGT values taken before and after drainage in all patients were compared. Results: Biliary drainage was technically successful in all patients.İn the first two weeks after biliary drainage, 38 cases (86%) had a general condition improvement, weakness and itching decreased. The mean TB;19,41 ± 9,09; 9,39 ± 15,34, ALP; 701,27 ± 352,53 ; 357,48 ± 268,70, ALT; 122,45 ± 75,42; 62,91 ± 61,90, AST; 129,14 ± 84,31; 94,93 ± 118,79, GGT; 684,48 ± 428,83; 322,39 ± 253,26 values taken before and after drainage in all patients were compared and a significant decrease was found in the post-procedure values (p lt;0,050). In the follow-up, minor complications were observed in 10 patients (22.7%). Conclusion: It is necessary to prevent inoperable patients from entering hepato-renal failure in order to prolong life time as much as possible. PBD and stent applications significantly improves impaired liver function, allowing the patients general condition improvement. Low complication rates and quickyl improving general condition of patients without need for another surgery gradually increase the value of this radiological intervention.